Understanding intentionally and non-intentionally added substances and associated threshold of toxicological concern in post-consumer polyolefin for use as food packaging materials - Khairun Tumu; Keith Vorst; Greg Curtzwiler (Heliyon, 2024)
The use of post-consumer recycled (PCR) polymers in food contact materials (FCMs) can facilitate achieving a circular economy by reducing environmental waste and landfill accumulation. This study aimed to identify potentially harmful substances, including non-intentionally added substances (NIAS) and unapproved intentionally added substances (IAS), in polyolefin samples from material recovery facilities using gas-chromatography mass-spectrometry. Selected phthalates and bisphenols were quantified by targeted gas-chromatography tandem mass-spectrometry. The analysis detected 9 compounds in virgin polymers and 52 different compounds including alcohols, hydrocarbons, phenols in virgin and hydrocarbons, aromatic, phthalates, organic acids, per- and polyfluoroalkyl substances (PFAS) in PCR polymers. The Cramer classification system was used to assesses the Threshold of Toxicological Concern associated with the detected compounds. The PCR sample showed a slightly higher proportion of Cramer Class III compounds (48.08 %) than the virgin sample (44.44 %), indicating higher toxicity potential. Quantification detected bisphenols only in PCR material including BPA (2.88 ± 0.53 μg/g), BPS (5.12 ± 0.003 μg/g), BPF (3.42 ± 0.01 μg/g), and BADGE (4.638 μg/g). Phthalate concentrations were higher in PCR than virgin samples, with the highest levels detected as DIDP, at 6.18 ± 0.31 μg/g for PCR and 6.04 ± 0.02 for virgin. This study provides critical understanding of the safety and potential risks associated with using PCR polyolefins from different sources in food contact applications.